Just How Stupid Are We? : Facing the Truth About the American Voter. - Shenkman, Rick (Basic Books, 2009)
Fifty percent of Americans can name four characters from "The Simpsons," but only two out of five can name all three branches of the federal government. No more than one in seven can find Iraq on a map. Just how stupid are we? Pretty stupid.